Preparation method of MnOx-FeOx-titanium silicalite molecular sieve low-temperature denitration catalyst

Through the preparation method of the MnOx-FeOx-titanium silicon molecular sieve low-temperature denitrification catalyst, the existing denitrification catalyst has been solved, and the problem of low denitrification rate and susceptible to water and sulfur under low temperature conditions has been achieved, achieving efficient NOx conversion and improving economic benefits.

CN119215978APending Publication Date: 2024-12-31PEKING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411354027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-20
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing denitrification catalysts have a low denitrification rate under low temperature conditions, are susceptible to water and sulfur dioxide, and have complex preparation methods and low economic benefits.

Method used

The preparation method of low-temperature denitrification catalyst of MnOx-FeOx-titanium silicon molecular sieve was adopted to prepare titanium silicon molecular sieve carriers by hydrothermal method, and the MnOx-FeOx load was introduced by impregnation method to control the Ti/Si molar ratio and manganese-ferromanganese mass ratio and optimize the roasting parameters To improve the low-temperature denitrification performance of the catalyst.

Benefits of technology

At 120°C, it exhibits an nitrogen oxide conversion efficiency of more than 90%, has excellent NOx conversion efficiency, improves the surface acidity and redox properties of the catalyst, enhances water and sulfur resistance, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215978A_ABST
    Figure CN119215978A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a MnOx-FeOx-titanium silicalite molecular sieve low-temperature denitration catalyst, which comprises the following steps: dropwise adding ethyl silicate into a tetrapropylammonium hydroxide aqueous solution, stirring, simultaneously dissolving tetrabutyl titanate into isopropanol, independently hydrolyzing, mixing the two solutions, and reacting at the temperature of 60-80 DEG C for 2-3 hours to obtain the MnOx-FeOx-titanium silicalite molecular sieve low-temperature denitration catalyst. Heating to remove alcohol and supplementing evaporated water in time to obtain a mixture; transferring the mixture into a reaction kettle for hydrothermal treatment, cooling to room temperature, centrifuging, washing and drying to obtain white precipitate; grinding the white precipitate, transferring to a muffle furnace, and roasting to obtain a carrier; and dissolving manganous nitrate and ferric nitrate in deionized water to form a mixed solution, immersing the carrier powder into the mixed solution, stirring, drying to obtain a solid, grinding the solid, transferring into a muffle furnace, and roasting to obtain the MnOx-FeOx-TS-1 catalyst. According to the preparation method disclosed by the invention, the Ti element is introduced into the carrier under the condition that the pore diameter structure is not changed, so that the MnOx-FeOx catalyst loaded on TS-1 shows excellent NOx conversion efficiency in a low-temperature NH3-SCR (Selective Catalytic Reduction) reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of low-temperature denitration catalysts, in particular to a MnO x -FeO x -Preparation method of titanium silicon molecular sieve low-temperature denitrification catalyst. Background Art

[0002] NO x NO and SO2 are the main pollutants in the atmosphere and the main source of acid rain. Human activities, fuel combustion, industrial production, etc. may produce NO. x , NO x Mainly including N2O, NO, NO2, N2O3, N2O4 and N2O5, etc. x Pollution has become an increasingly serious global problem. Selective catalytic reduction (SCR) technology converts NO and NO2 into N2 under the action of NH3 and catalyst. SCR technology can achieve high NO x Reduction rate (85-95%), flue gas NO x Emission levels can be reduced to 100-200mg / Nm 3 SCR technology is considered to be the most thorough NO reduction technology due to its huge reduction potential and no reaction by-product generation. x Emission reduction technology.

[0003] Currently, many patents for SCR denitrification catalysts have been applied for. CN102921403A discloses a method for preparing V2O5-WO3 / TiO2 powder for denitrification catalysts. The vanadium-tungsten precursor is simultaneously combined with metatitanic acid by an impregnation method. After calcination, the vanadium-tungsten component is evenly combined on the surface of titanium dioxide. The powder prepared by this method has excellent denitrification performance. Under the condition of 100% flue gas conditions, the denitrification rate can reach more than 95% in the temperature window of 320-400°C. CN110523436A discloses a novel powdered denitration catalyst, comprising active components, auxiliary agents and additives, wherein the active components are Fe oxide and Mn oxide, the auxiliary agents are one or more oxides of Ce, La, Er, Si, Al, Ca, Ti, Au or Pt, and the additives are a mixture of one or two of activated carbon or urea and one or two of melamine or glucose. Finally, the active components, auxiliary agents and additives obtained by roasting are fully mixed and ball-milled to obtain a novel powdered denitration catalyst. The prepared catalyst component is environmentally friendly and can remove NO. x The active temperature is high and the window is wide, and denitrification can be effectively achieved within the temperature range of 700-1200℃.

[0004] Current denitrification catalysts also have the following disadvantages:

[0005] (1) The denitrification rate is high only at high temperatures and is not suitable for use under low temperature conditions;

[0006] (2) Under actual denitrification conditions, the flue gas contains a small amount of water and sulfur dioxide, which can easily affect the catalyst and cause a decrease in the denitrification rate;

[0007] (3) The catalyst preparation method is complicated, the raw materials used are expensive, and the economic benefits are low. Summary of the Invention

[0008] The purpose of the present invention is to provide a MnO x -FeO x - A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst to solve the problem that the above-mentioned denitration catalyst can only be used at high temperatures and is easily deactivated by water and sulfur dioxide.

[0009] To achieve the above object, the present invention provides a MnO x -FeO x -The preparation method of titanium silicon molecular sieve low-temperature denitration catalyst comprises the following steps:

[0010] (1) Preparation of carrier

[0011] Ethyl silicate is added dropwise to a tetrapropylammonium hydroxide aqueous solution and stirred. Tetrabutyl titanate is dissolved in isopropyl alcohol and hydrolyzed separately. The two solutions are then mixed, heated to remove alcohol and the evaporated water is promptly replenished to obtain a mixture.

[0012] The mixture was then transferred to a reactor for hydroheating, cooled to room temperature, centrifuged, washed, and dried to obtain a white precipitate;

[0013] The white precipitate was ground and then transferred to a muffle furnace for calcination to obtain titanium silicate molecular sieve TS-1, i.e., the support;

[0014] (2)MnO x -FeO x -Preparation of TS-1 catalyst

[0015] Manganese nitrate and ferric nitrate are dissolved in deionized water to form a mixed solution, the carrier powder is immersed in the mixed solution, stirred and dried to obtain a solid, and the solid is ground and transferred to a muffle furnace for calcination to obtain MnO x -FeO x -TS-1 catalyst.

[0016] Preferably, the Ti / Si molar ratio of tetrabutyl titanate and ethyl silicate added in step (1) is (0-0.05):1.

[0017] Preferably, the stirring temperature and the hydrolysis temperature in step (1) are both 40° C., the hydrolysis time is 2 h, and the heating temperature for removing alcohol is 80° C., and the time is 3 h.

[0018] Preferably, the hydrothermal temperature in step (1) is 160° C. and the time is 48 h.

[0019] Preferably, the calcination parameters in step (1) are calcination at a heating rate of 2°C / min to 550°C for 6h in an air atmosphere.

[0020] Preferably, the mass ratio of manganese to iron in step (2) is (1-5):(1-5).

[0021] Preferably, in step (2), MnO x -FeO x The loading amount is 1-10 wt.%.

[0022] Preferably, in step (2), the prepared carrier powder is immersed in the mixed solution, magnetically stirred at room temperature for 2 hours, the temperature is raised to 100° C. to evaporate excess water, and the mixture is transferred to an oven at 80° C. and dried overnight to obtain a solid.

[0023] Preferably, the calcination parameters in step (2) are calcination in air atmosphere at a heating rate of 5°C / min to 500°C for 4h.

[0024] Preferably, in step (2), the mass ratio of manganese to iron is 3:2, MnO x -FeO x The loading amount was 5 wt.%.

[0025] Therefore, the present invention adopts a MnO x -FeO x -The preparation method of titanium silicon molecular sieve low-temperature denitration catalyst has the following beneficial effects:

[0026] (1) The catalyst showed a nitrogen oxide conversion efficiency of more than 90% at 120°C, indicating that the MnO synthesized by the present invention x -FeO x -TS-1 catalyst can be used at low temperatures and has a wider range of applications;

[0027] (2) The carrier introduces Ti element without changing the pore structure, which makes the MnO loaded on TS-1 x -FeO x The catalyst showed excellent NO removal in low-temperature NH3-SCR reaction. x transformation efficiency;

[0028] (3) The Ti element in the carrier promotes the Mn 4+The formation of ions improves the surface acidity and redox properties of the catalyst, which is beneficial to promoting low-temperature denitrification.

[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the denitration performance curve of the catalyst of Examples 1-3 in the temperature range of 90-270°C;

[0031] Figure 2 is the denitration performance curve of the catalyst of Example 1-3 after H2O is added;

[0032] Figure 3 is a graph showing the denitration performance of the catalysts of Examples 1-3 after addition of SO2;

[0033] Figure 4 is the H2-TPR spectrum of the catalyst of Example 1-3;

[0034] Figure 5 is the NH3-TPD spectrum of the catalyst of Example 1-3;

[0035] Figure 6 is an infrared spectrum of NH3 in situ adsorption on the catalyst surface of Example 1-3 in the temperature range of 60 to 330°C;

[0036] Figure 7 is the XRD spectrum of the catalyst of Example 1-3;

[0037] Figure 8 is the FT-IR spectrum of the catalyst of Example 1-3;

[0038] Figure 9 The SEM and TEM images of the catalysts of Examples 1-3 are shown;

[0039] Figure 10 This is the EDS surface scan spectrum of the TS-1 carrier;

[0040] Figure 11 : EDS surface scan spectra of the catalysts of Examples 1-3;

[0041] Figure 12 is the N2 adsorption / desorption isotherms of the support and catalyst;

[0042] Figure 13 XPS fine spectra of Mn 2p, Fe 2p and O1s of different catalysts;

[0043] Figure 14 These are the TG curves of the sulfur-resistant samples of catalysts with different supports in the temperature range of 20 to 1000°C. DETAILED DESCRIPTION

[0044] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and specific operation process, but the present invention is not limited to this embodiment.

[0045] Example 1

[0046] A MnO x -FeO x -The preparation method of titanium silicon molecular sieve low-temperature denitration catalyst comprises the following steps:

[0047] (1) Preparation of vector TS-1

[0048] The carrier TS-1 was prepared by a hydrothermal method, in which tetrapropylammonium hydroxide (TPAOH) was used as a microporous template, ethyl silicate (TEOS) and tetrabutyl titanate (TBOT) were used as hydrolyzed silicon and titanium sources, respectively, and the silicon-titanium molar ratio in the carrier was controlled to be 1:0.03.

[0049] Specifically, 12 g of TEOS was added dropwise to a 12.8 g TPAOH aqueous solution under constant magnetic stirring at 40°C. At the same time, a certain amount of TBOT was dissolved in 10 g of isopropanol. After being hydrolyzed separately at 40°C for 2 h, the two mixed solutions were mixed and heated to 80°C for 3 h to remove the alcohol. The evaporated water was replenished in time. The mixture was then transferred to a 50 mL reactor and hydroheated in a 160°C oven for 48 h. After the reactor cooled to room temperature, the mixture was centrifuged to obtain a white precipitate, which was washed three times with deionized water and ethanol respectively, and dried in an 80°C oven overnight.

[0050] Finally, the white precipitate of the sample was ground and transferred to a muffle furnace. It was calcined at 550°C at a heating rate of 2°C / min for 6 h in an air atmosphere. The prepared support was labeled TS-1-0.03.

[0051] (2)MnO x -FeO x -Preparation of TS-1 catalyst

[0052] Using the prepared TS-1-0.03 as the carrier, the MnO with a total metal loading of 5 wt.% was prepared by impregnation method. x -FeO x For supported catalyst, the mass ratio of manganese to iron is controlled to be Mn:Fe=3:2.

[0053] Specifically, manganese nitrate and ferric nitrate in the above-mentioned mass ratio were first dissolved in 20 mL of deionized water. The prepared TS-1-0.03 carrier powder was then immersed in the mixed solution. After magnetic stirring at room temperature for 2 hours, the temperature was raised to 100°C to evaporate excess water, and the mixture was transferred to an 80°C oven for drying overnight.

[0054] Finally, the sample was ground and transferred to a muffle furnace. It was calcined at 500 °C for 4 h at a heating rate of 5 °C / min under air atmosphere. The prepared catalyst was labeled Mn3Fe2 / TS-1-0.03.

[0055] Example 2

[0056] A MnO x -FeO x -The preparation method of titanium silicon molecular sieve low-temperature denitration catalyst comprises the following steps:

[0057] (1) Preparation of vector TS-1

[0058] The carrier TS-1 was prepared by a hydrothermal method, in which tetrapropylammonium hydroxide (TPAOH) was used as a microporous template, ethyl silicate (TEOS) and tetrabutyl titanate (TBOT) were used as hydrolyzed silicon and titanium sources, respectively, and the silicon-titanium molar ratio in the carrier was controlled to be 1:0.05.

[0059] Specifically, 12 g of TEOS was added dropwise to a 12.8 g TPAOH aqueous solution under constant magnetic stirring at 40°C. At the same time, a certain amount of TBOT was dissolved in 10 g of isopropanol. After being hydrolyzed separately at 40°C for 2 h, the two mixed solutions were mixed and heated to 80°C for 3 h to remove the alcohol. The evaporated water was replenished in time. The mixture was then transferred to a 50 mL reactor and hydroheated in a 160°C oven for 48 h. After the reactor cooled to room temperature, the mixture was centrifuged to obtain a white precipitate, which was washed three times with deionized water and ethanol respectively, and dried in an 80°C oven overnight.

[0060] Finally, the white precipitate of the sample was ground and transferred to a muffle furnace. It was calcined at 550°C at a heating rate of 2°C / min for 6 h in an air atmosphere. The prepared support was labeled TS-1-0.05.

[0061] (2)MnO x -FeO x -Preparation of TS-1 catalyst

[0062] Using the prepared TS-1-0.05 as the carrier, the MnO with a total metal loading of 5 wt.% was prepared by impregnation method. x -FeO x For supported catalyst, the mass ratio of manganese to iron is controlled to be Mn:Fe=3:2.

[0063] Specifically, manganese nitrate and ferric nitrate in the above-mentioned mass ratio were first dissolved in 20 mL of deionized water. The prepared TS-1-0.05 carrier powder was then immersed in the mixed solution. After magnetic stirring at room temperature for 2 hours, the temperature was raised to 100°C to evaporate excess water, and the mixture was transferred to an 80°C oven for drying overnight.

[0064] Finally, the sample was ground and transferred to a muffle furnace. It was calcined at 500 °C for 4 h at a heating rate of 5 °C / min under air atmosphere. The prepared catalyst was labeled Mn3Fe2 / TS-1-0.05.

[0065] Example 3

[0066] A MnO x -FeO x - A method for preparing a silicon molecular sieve low-temperature denitration catalyst, comprising the following steps:

[0067] (1) Preparation of carrier S-1

[0068] Support S-1 was prepared by a hydrothermal method, in which tetrapropylammonium hydroxide (TPAOH) was used as a microporous template and tetraethyl silicate (TEOS) was used as a hydrolyzed silicon source.

[0069] Specifically, 12 g of TEOS was added dropwise to a 12.8 g TPAOH aqueous solution under constant magnetic stirring at 40°C. After hydrolysis at 40°C for 2 h, the mixture was heated to 80°C for 3 h to remove the alcohol. The evaporated water was replenished in time. The mixture was then transferred to a 50 mL reactor and hydroheated in a 160°C oven for 48 h. After the reactor cooled to room temperature, the mixture was centrifuged to obtain a white precipitate, which was washed three times with deionized water and ethanol respectively, and dried in an 80°C oven overnight.

[0070] Finally, the white precipitate of the sample was ground and transferred to a muffle furnace. It was calcined at 550°C at a heating rate of 2°C / min for 6 h in an air atmosphere to obtain the Silicalite-1 carrier. The prepared carrier was labeled S-1.

[0071] (2) Preparation of Mn3Fe2 / Silicalite-1 Catalyst

[0072] Using the prepared S-1 as the support, MnO with a total metal loading of 5 wt.% was prepared by impregnation method. x -FeO x For supported catalyst, the mass ratio of manganese to iron is controlled to be Mn:Fe=3:2.

[0073] Specifically, manganese nitrate and ferric nitrate in the above-mentioned mass ratio were first dissolved in 20 mL of deionized water. The prepared S-1 carrier powder was then immersed in the mixed solution. After magnetic stirring at room temperature for 2 hours, the temperature was raised to 100°C to evaporate excess water, and the mixture was transferred to an 80°C oven for drying overnight.

[0074] Finally, the sample was ground and transferred to a muffle furnace. It was calcined at 500°C for 4 h at a heating rate of 5°C / min in an air atmosphere to obtain a Mn3Fe2 / Silicalite-1 catalyst. The prepared catalyst was labeled Mn3Fe2 / S-1.

[0075] Example 4

[0076] The catalysts prepared in Examples 1-3 were tested for NH3-SCR activity.

[0077] The test method is as follows: The NH3-SCR test of the catalyst is carried out in a fixed bed reactor. The reaction gas composition is 500ppm NO, 500ppm NH3, 3vol.% O2, 10vol.% H2O and 50ppm SO2 (used for water and sulfur resistance reaction), and N2 is used as the balance gas. 200mg of catalyst (40-60 mesh) is transferred to a quartz reaction tube with an inner diameter of 6mm. After being purged with N2 at 200℃ for 30 minutes, it is cooled to room temperature and the reaction gas is introduced to adsorb until saturation. The NH3-SCR reaction is carried out in the range of 90-300℃ and the space velocity is 18000h -1 When the reaction reaches a predetermined stable state, the concentrations of NO and NO2 after the reaction are measured by a portable flue gas analyzer (TestoPro350). x The conversion rate is calculated by the following formula:

[0078] Where ([NO x ]=[NO]+[NO2]).

[0079] Figure 1 The denitration performance curve of the catalyst prepared in Example 1-3 in the temperature range of 90-270°C is shown. Figure 1 It can be seen that the Mn3Fe2 / TS-1-0.03 catalyst showed more than 90% NO at 120 °C. x The conversion efficiency is higher than that of Mn3Fe2 / S-1 (i.e. Mn3Fe2 / Silicalite-1) catalyst at the same temperature. xThe conversion efficiency is nearly 30% higher. In addition, the denitrification activity of Mn3Fe2 / TS-1-0.03 and Mn3Fe2 / TS-1-0.05 catalysts doped with Ti species are significantly improved compared with Mn3Fe2 / S-1 catalyst in the low temperature range, especially below 150°C. Among them, the Mn3Fe2 / TS-1-0.03 catalyst with the best denitrification activity is significantly improved at 18,000 h. -1 Under the condition of space velocity, more than 80% of NO can be maintained in the temperature range of 110-230℃. x Conversion efficiency. In the high temperature range above 240℃, the NO conversion efficiency of Mn3Fe2 / S-1 and Mn3Fe2 / TS-1-0.03 catalysts is x The conversion efficiency is reduced due to the increase of side reactions, but the Mn3Fe2 / TS-1-0.05 catalyst can still maintain more than 80% of NO x Conversion efficiency. It can be seen that the incorporation of Ti species in the support has an important influence on the physical and chemical properties of the catalyst surface, thereby improving the activity of the catalyst in low-temperature denitrification.

[0080] The molecular sieve support is very sensitive to H2O and SO2. Under actual NH3-SCR denitrification conditions, especially the flue gas from coal-fired power plants contains a small amount of H2O and SO2. Therefore, the effect of H2O and SO2 on the denitrification performance of the catalyst was further studied at 180°C. Figure 2 It shows that after H2O is added, MnO x -FeO x Changes in the denitrification performance of the catalyst. Figure 2 When 10 vol.% H2O was added to the reaction, the Mn3Fe2 / TS-1-0.03 and Mn3Fe2 / TS-1-0.05 catalysts still maintained about 95% of NO x The conversion efficiency is basically the same as the denitrification efficiency under the condition of no H2O, while the NO x The conversion efficiency dropped by more than 5% and remained at around 90%. x The conversion efficiency quickly returned to the level achieved in the absence of H2O, demonstrating that the deactivation of the catalyst by H2O is reversible. Catalyst deactivation after the addition of H2O is primarily due to competitive adsorption between H2O and NH3 on the catalyst surface. H2O occupies adsorption sites on the catalyst surface previously reserved for NH3, resulting in a decrease in the catalyst's denitrification performance. The incorporation of Ti species into the support increases the hydrophobicity of the catalyst surface, making H2O adsorption more difficult, thereby reducing its impact on the catalyst's denitrification activity.

[0081] Figure 3The effect of SO2 in the reaction gas on the denitrification performance of the catalyst is demonstrated. When 50ppm SO2 is added to the reaction gas, the Mn3Fe2 / S-1 catalyst maintains more than 90% NO in about 3 hours. x The conversion efficiency then dropped rapidly to 50% and below. In contrast, the Mn3Fe2 / TS-1-0.03 and Mn3Fe2 / TS-1-0.03 catalysts maintained over 90% activity for 4h and 6h in the presence of SO2. x -FeO x The deactivation of the catalyst is irreversible. The presence of Ti species in the carrier slows down the reaction between SO2 and the active components to a certain extent, thus extending the service life of the catalyst.

[0082] Example 5

[0083] Catalyst surface redox analysis (H2-TPR).

[0084] The redox properties of the catalyst surface are closely related to its catalytic activity in the NH3-SCR reaction. Therefore, the H2-TPR experiment was used to characterize the redox properties of the catalyst surface. The test results are as follows: Figure 4 As shown in Table 1. Figure 4 As shown, all catalysts exhibit three reduction peaks between 400 and 700°C. The reduction peak at 430°C is associated with the reduction of MnO2 and Fe2O3 (i.e., MnO2 → Mn2O3, Mn2O3 → Mn3O4, and Fe2O3 → FeO). The reduction peak at 580°C can be attributed to the reduction of Mn3O4, while the reduction peaks above 660°C are associated with the reduction of FeO. Table 1 shows the integrated areas of the reduction peaks for each catalyst. As can be seen, the total reduction peak area for the Mn3Fe2 / TS-1-0.03 catalyst reaches 776 a.u. after the introduction of Ti species into the support, an increase of over 20% compared to the Mn3Fe2 / S-1 catalyst. Since the reduction peak area of ​​the catalysts corresponds to H2 consumption, the introduction of Ti species into the support significantly enhances the redox properties of the catalyst surface, which is beneficial for promoting the low-temperature NH3-SCR reaction.

[0085] Table 1 H2 reduction peak temperature and consumption of catalysts

[0086]

[0087] Example 6

[0088] Analysis of acidic sites on catalyst surface

[0089] The surface acidity of the catalyst is another very important factor affecting the low-temperature NH3-SCR reaction activity. Therefore, the surface acidity of the catalyst was analyzed by NH3-TPD experiment. The desorption curve and integral calculation results of NH3 are shown as follows: Figure 5 As shown in Table 2. Figure 5 It can be seen that the NH3 desorption curve of the Mn3Fe2 / S-1 catalyst shows two desorption peaks, marked as Ⅰ and Ⅱ, corresponding to weak acid sites (<200℃) and medium acid sites (200~400℃), respectively. However, there are four and three desorption peaks in the NH3 desorption curves of the Mn3Fe2 / TS-1-0.03 and Mn3Fe2 / TS-1-0.05 catalysts, respectively. The newly added desorption peaks can be attributed to the medium (200~400℃) and high (>400℃) acid sites, which indicates that the newly added Lewis acid sites are related to the incorporation of Ti elements in the support, and therefore are conducive to promoting the adsorption of NH3. Figure 5 The total surface acidity of the catalysts was calculated by integrating the NH3 desorption peaks of each catalyst in Table 2. As can be seen from Table 2, the total surface acidity of the Mn3Fe2 / TS-1-0.03 and Mn3Fe2 / TS-1-0.05 catalysts is much greater than that of the Mn3Fe2 / S-1 catalyst. In particular, the total surface acidity of the Mn3Fe2 / TS-1-0.03 catalyst is approximately 50% higher than that of the Mn3Fe2 / S-1 catalyst. Combined with these experimental results, the incorporation of Ti species into the support significantly enhances the surface acidity of the catalysts, facilitating NH3 adsorption and thereby improving the activity of the low-temperature NH3-SCR reaction.

[0090] Table 2MnO x -FeO x NH3 desorption peak temperature and total acid content of the catalyst

[0091]

[0092] Figure 6 The in-situ infrared spectrum of NH3 adsorption on the catalyst surface in the temperature range of 60-300℃ is shown, which further distinguishes the Acidic sites (labeled as B acid) and Lewis acidic sites (labeled as L acid). The center of the band is at 1602-1605 cm -1 , 1225~1227cm -1 , 1142~1163cm -1 and 1059~1064cm -1 The bands at 1428-1448 cm can be attributed to the symmetric and asymmetric bending vibrations of the coordinated NH3 adsorbed on the L acid site. -1and 1737~1748cm -1 The band at can be attributed to NH4 adsorbed on the B acid site + Species. The band center is at 1550~1554cm -1 and 1302~1324cm -1 The band at can be attributed to the -NH2 species transformed from the coordinated NH3. Figure 6 It can be found that with the increase of temperature, the spectral band related to the B acid site decreases more significantly than the spectral band related to the L acid site. This shows that the NH3 species adsorbed on the L acid site on the surface is more stable at high temperature. In addition, by comparing the spectra of Mn3Fe2 / TS-1-0.03 catalyst, Mn3Fe2 / TS-1-0.05 catalyst and Mn3Fe2 / S-1 catalyst, it can be found that after the Ti species are doped into the support, the spectral band center is at 1602~1605cm -1 and 1428~1448cm -1 The band intensity at the position is significantly enhanced, which shows that the Mn3Fe2 / TS-1-0.03 catalyst and the Mn3Fe2 / TS-1-0.05 catalyst can provide more adsorbed NH3 for the NH3-SCR reaction compared with the Mn3Fe2 / S-1 catalyst, which helps to improve the catalytic activity.

[0093] Example 7

[0094] Characterize the catalyst.

[0095] (1) ICP characterization

[0096] The elemental contents of the catalysts were determined by ICP and are summarized in Table 3. Table 3 shows that the mass fractions of the active metal components, Mn and Fe, in the catalysts are very close to the initial charge ratio, indicating that there is virtually no loss of Mn and Fe during the impregnation process. Furthermore, the Mn and Fe contents of the different supports are essentially consistent, with no significant differences.

[0097] Table 3 Chemical composition of catalysts

[0098]

[0099] (2) XRD characterization

[0100] Figure 7 is the powder XRD spectrum of the support and catalyst. Figure 7As can be seen, all three supports exhibit distinct characteristic peaks at 7.9°, 8.8°, 23.1°, 23.8°, and 24.3°, indicating that all three types of supports possess a typical MFI pore structure. Furthermore, the characteristic peak at 25.4° attributable to anatase is absent from TS-1-0.03 but appears in the spectrum of TS-1-0.05, indicating that the excess Ti species forms a small amount of anatase in TS-1-0.05.

[0101] (3) FT-IR characterization

[0102] Figure 8 The FT-IR spectra of the three carriers are shown in Figure 2, where the peaks at 433, 545-546, 799-803, 1074-1075 and 1223-1225 cm -1 The characteristic peak of 957-958 cm belongs to the MFI pore structure of the carrier, while -1 The characteristic peaks of TiO2 demonstrate the incorporation of Ti species into the support framework. Due to the very low metal loading of the catalysts, the XRD patterns of the catalysts lack characteristic peaks associated with surface metal oxides. Furthermore, all catalysts exhibited clear peaks consistent with the support, indicating that the support structure was not disrupted during the impregnation process.

[0103] (4) TEM characterization

[0104] The morphology of the catalyst was further studied using SEM and TEM. Figure 9 As shown in the SEM images of the carrier, it can be seen that the carriers all have a typical MFI structure with a particle size of about 150nm. However, the incorporation of Ti species causes some nanoscale wrinkles on the surface of the carrier, which is mainly due to the size difference between Ti atoms and Si atoms. Comparing the TEM images of the carrier and the catalyst, it can be seen that the MnO x and FeO x After the catalyst was added, a number of nano-sized particles appeared on the surface of the support, which were presumably active metal oxides. To further confirm the composition of these small particles on the catalyst surface, X-ray energy spectrum analysis was used to scan the support and catalyst surface. Figure 10 This is the EDS surface scan spectrum of the Ti-containing carrier. It can be seen that the distribution of Ti species is extremely similar to that of Si and O atoms, which indirectly explains the existence of Ti-O-Si structure in the carrier. Figure 11 The EDS surface scan spectra of various elements in the catalyst show that the impregnated Mn and Fe species are evenly dispersed on the support surface. In addition, the surface scan spectra of Mn and Fe species are very similar, indicating that due to the strong interaction between metal oxides, Mn and Fe species are likely to be FeMnO xTherefore, the introduction of Ti species in the support does not change the textural properties of the catalyst, but due to the difference in atomic size between Ti and Si, fine wrinkles will be generated on the catalyst surface, which can provide better reaction active sites for the catalytic reaction.

[0105] (5) BET characterization

[0106] The N2 adsorption / desorption isotherms of the support and catalyst are shown in Figure 2. Figure 12 The corresponding texture properties are summarized in Table 4. Figure 12 The N2 adsorption / desorption isotherms of the support and catalyst can be classified as type I, indicating that all samples have microporous structures. As can be seen from Table 4, the specific surface area, total pore volume and average pore diameter of support S-1 are 454.31 m 2 / g, 0.32cm 3 / g and 2.85nm. When Ti species were introduced into the support structure, the specific surface area, total pore volume and average pore diameter of TS-1-0.03 and TS-1-0.05 increased by about 10%, which was mainly due to the difference in atomic size between the incorporated Ti and the Si in the support. x and FeO x After the addition of the catalysts, the specific surface area and total pore volume of the three catalysts decreased by about 10%, while the average pore diameter remained basically the same. x and FeO x The coexistence of species on the surface of the catalyst does not change the pore structure of the carrier, which is consistent with the conclusion obtained from XRD.

[0107] Table 4 Texture data of support and catalyst

[0108]

[0109] (6) XPS characterization

[0110] Figure 13 The XPS fine spectra of Mn 2p, Fe 2p and O1s of different catalysts are shown in Table 5 and Table 6 respectively. Figure 13 It can be seen that the Mn 2p fine spectrum is mainly composed of two main peaks, which are respectively attributed to Mn 2p 3 / 2 (peak at about 642 eV) and Mn 2p 1 / 2 (peak is about 654eV), where Mn 2p 3 / 2 The peaks can be attributed to Mn 2+ ,Mn 3+ and Mn 4+The Fe 2p fine spectrum can be fitted by three independent orbital peaks (peaks are about 642eV, 643eV and 645eV). Similarly, the Fe 2p fine spectrum can be fitted by five independent orbital peaks, which are respectively attributed to Fe 3 / 2 and Fe 1 / 2 Fe 2+ ,Fe 3+ and satellite peaks (peaks at approximately 710 eV, 713 eV, 724 eV, 726 eV, and 718 eV). The O 1s fine spectrum can be fitted by two independent orbital peaks, corresponding to the lattice oxygen species (peak at approximately 530 eV, labeled O α ) and surface adsorbed oxygen species (peak at about 533 eV, labeled O β ).

[0111] Mn 4+ It plays an important role in the low-temperature NH3-SCR reaction. The Mn content in the catalyst was calculated based on the peak separation results. 4+ / (Mn 4+ +Mn 3+ +Mn 2+ ) ratio, and is also closely related to the denitrification activity of the catalyst Fe 3+ / (Fe 3+ +Fe 2+ ) and O β / (O α +O β ) are summarized in Table 6. As can be seen from Table 6, the Mn in the Mn3Fe2 / TS-1-0.03 catalyst 4+ / (Mn 4+ +Mn 3+ +Mn 2+ ) ratio is 34.6%, which is higher than that of Mn in Mn3Fe2 / S-1 catalyst. 4+ The ratio (25.0%) increased by nearly 10%. 4+ The increase in the ratio can be attributed to the redox reaction between Mn and Ti species, such as Mn 3+ +Ti 4+ =Mn 4+ +Ti 3+ ,Mn 2+ +2Ti 4 + =Mn 4+ +2Ti 3+ Mn in Mn3Fe2 / TS-1-0.05 catalyst 4+The ratio remains basically unchanged, which can be attributed to the anatase formed on the support. The excess Ti in the Ti-containing support TS-1-0.05 forms anatase on the support surface, which inhibits the electron transfer between Mn species and the molecular sieve support. When Ti species are introduced into the support, Fe 3+ / (Fe 3+ +Fe 2+ ) also decreased slightly, which can be attributed to the electron transfer between Fe and Ti species: Fe 3+ +Ti 3+ =Fe 2+ +Ti 4+ For O species in the catalyst, the adsorption of oxygen (O β ) species have excellent migration ability, so in the low-temperature NH3-SCR reaction, they are more effective than the lattice oxygen (O α ) species are more reactive. As shown in Table 6, the incorporation of Ti species in the support increases the O β / (O α +O β ) ratio, however, the excess Ti species consumes part of the surface adsorbed oxygen due to the formation of anatase on the catalyst surface.

[0112] In summary, the redox reaction occurred between the Ti species incorporated into the support and the loaded active material, which made the Mn3Fe2 / TS-1-0.03 catalyst have the highest Mn 4+ and surface adsorbed oxygen (O β ) ratio, thus showing the best catalytic performance in low-temperature NH3-SCR reaction.

[0113] Table 5 Catalyst surface atomic concentration

[0114]

[0115] Table 6 Valence distribution of elements on catalyst surface

[0116]

[0117] (7) Catalyst thermogravimetric analysis (TG)

[0118] Denitrification catalysts with manganese oxide as the active component are very sensitive to SO₂ in flue gas. The active component easily undergoes an irreversible chemical reaction with SO₂, leading to catalyst deactivation. Therefore, TG analysis was performed on samples of catalysts with different supports after sulfur treatment to investigate the SO₂ deactivation process. Figure 14 The TG curves of the samples of catalysts with different supports after sulfur resistance in the temperature range of 20 to 1000°C are shown in Figure 2. Figure 14As can be seen from the data, the weight loss of the sulfur-treated Mn3Fe2 / S-1 catalyst samples proceeds in three stages. Weight loss below 150°C is attributed to surface moisture adsorption. Weight loss between 150 and 400°C can be attributed to the decomposition of NH4HSO4 and (NH4)2SO4 formed on the catalyst surface. Weight loss above 400°C is primarily due to the decomposition of MnSO4 formed on the catalyst surface. In contrast, the sulfur-treated Mn3Fe2 / TS-1-0.03 and Mn3Fe2 / TS-1-0.05 catalysts exhibit two distinct weight loss peaks in the 600-800°C temperature range, which can be attributed to the decomposition of Ti(SO4)2 and Ti2(SO4)3 formed by the Ti species in the support and SO2 in the flue gas. This surface Ti species in the support hinder the reaction of SO2 species with the surface active components, thereby extending the catalyst's service life in SO2-laden flue gas.

[0119] Therefore, the present invention adopts a MnO x -FeO x -Preparation method of titanium silicate molecular sieve low-temperature denitrification catalyst, the carrier introduces Ti element without changing the pore structure, and MnO loaded on TS-1 x -FeO x The catalyst showed excellent NO removal in low-temperature NH3-SCR reaction. x The incorporation of Ti into the support promotes the formation of high-valence Mn species on the surface, and adds new Lewis acid sites on the catalyst surface. In addition, the Ti element in the support enhances the redox properties of the catalyst surface, and the presence of Ti makes the catalyst surface more hydrophobic, thereby improving the water resistance of the catalyst. x -FeO x The catalyst will be more in line with the needs of large-scale industrial low-temperature denitrification.

[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A MnO x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: The following steps are involved: (1) Preparation of carrier Ethyl silicate is added dropwise to a tetrapropylammonium hydroxide aqueous solution and stirred, and tetrabutyl titanate is dissolved in isopropanol, and after hydrolysis, the two solutions are mixed, heated to remove alcohol, and evaporated water is replenished in time to obtain a mixture; The mixture was then transferred to a reactor for hydrothermal treatment, cooled to room temperature, centrifuged, washed, and dried to obtain a white precipitate; The white precipitate was ground and then transferred to a muffle furnace for calcination to obtain titanium silicalite molecular sieve TS-1, i.e., the carrier; (2) MnO x -FeO x - Preparation of TS-1 catalyst Manganese nitrate and iron nitrate are dissolved in deionized water to form a mixed solution, the carrier powder is immersed in the mixed solution, stirred and dried to obtain a solid, and the solid is ground and transferred to a muffle furnace for calcination to obtain MnO x -FeO x -TS-1 catalyst.

2. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: The Ti / Si molar ratio of tetrabutyl titanate and ethyl silicate added in step (1) is (0-0.05):

1.

3. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: The stirring temperature and hydrolysis temperature in step (1) are both 40°C, the hydrolysis time is 2h, and the heating temperature for removing alcohol is 80°C for 3h.

4. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: In step (1), the hydrothermal temperature is 160° C. and the time is 48 h.

5. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: The calcination parameters in step (1) are as follows: calcination at a heating rate of 2°C / min to 550°C for 6 hours in an air atmosphere.

6. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: The mass ratio of manganese to iron in step (2) is (1-5): (1-5).

7. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: In step (2), MnO x -FeO x The loading amount is 1-10wt.%.

8. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: In step (2), the prepared carrier powder is immersed in the mixed solution, and after magnetic stirring at room temperature for 2 hours, the temperature is raised to 100° C. to evaporate excess water, and the powder is transferred to an oven at 80° C. and dried overnight to obtain a solid.

9. A MnO according to claim 1 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: The calcination parameters in step (2) are calcination at a heating rate of 5°C / min to 500°C for 4h in an air atmosphere.

10. A MnO according to any one of claims 6 and 7 x -FeO x -A method for preparing a titanium silicon molecular sieve low-temperature denitration catalyst, characterized in that: In step (2), the mass ratio of manganese to iron is 3:2, MnO x -FeO x The loading amount is 5wt.%.

Citation Information

Patent Citations

  • Method for preparing V2O5-WO3 / TiO2 powder for making denitration catalyst

    CN102921403A

  • Powdery denitration catalyst and preparation method thereof

    CN110523436A